Pengaruh Kualitas Konten Dan Kualitas Sistem Virtual Reality Tourism Terhadap Niat Berperilaku (Studi Pada Objek Wisata Bandar Grissee Kabupaten Gresik) - Purnama, Muhammad Rouf; Setiyarini, Triana (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
Tourism is one of the important sectors for the economy in Indonesia. In addition to being an economic engine, the tourism industry is considered to be able to reduce the unemployment rate. Tourism is one of the keys to the national economy which is expected to be able to increase income through foreign exchange receipts. Data shows that the number of domestic tourist trips based on the number of provinces is the highest, namely East Java.One of the tourism objects that has something to see, something to do, something to buy indicators is the Bandar Grissee tourist destination in Gresik Regency. The Gresik Regency Tourism and Creative Economy, Culture, Youth and Sports Office innovates to increase tourist visits, namely through the concept of Virtual Reality Tourism. This study aims to find out how content quality and system quality have a positive and significant effect on behavioral intentions.The population of this study is visitors to Virtual Reality Tourism Bandar Grissee (Gresik Regency) and the number of samples used in this study is 97 respondents using the purposive sampling method. The data collection method used is through questionnaires. The data analysis in this study is using multiple linear regression analysis using IBM SPSS 25. The results showed that the content quality variable and the system quality variable had a positive and significant effect on behavioral intentions.